2018
DOI: 10.1007/s10815-018-1133-5
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous nonsense mutation Trp28X in the LHB gene causes male hypogonadism

Abstract: We identified a novel mutation in the LHB gene in a male patient with hypogonadism and provided evidence that LHB nonsense mutation can cause selective LH deficiency. We reconfirmed hCG treatment may restore male fertility due to LHB mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…Testis mutation results in decreased testis size, prominent Leydig cell hypoplasia, abnormalities in the expression of genes encoding steroid biosynthesis pathway enzymes, reduced testosterone levels, and blockage of spermatogenesis at the round spermatid stage. Yang et al [13] recognized a novel mutation in the LHB gene in a male patient with hypogonadism, which indicated that LHB mutation can cause selective LH insufficiency, resulting in infertility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Testis mutation results in decreased testis size, prominent Leydig cell hypoplasia, abnormalities in the expression of genes encoding steroid biosynthesis pathway enzymes, reduced testosterone levels, and blockage of spermatogenesis at the round spermatid stage. Yang et al [13] recognized a novel mutation in the LHB gene in a male patient with hypogonadism, which indicated that LHB mutation can cause selective LH insufficiency, resulting in infertility.…”
Section: Discussionmentioning
confidence: 99%
“…The β subunits, which originate from a gene complex on chromosome 19q13.32.2 during fetal life, result in chorionic gonadotropin initiating the growth of primordial Leydig cells and testosterone production, which in turn permits fetal masculinization [11]. Any alterations occurring in the luteinizing hormone receptor affect chorionic gonadotropin signaling in a male fetus, which results in clinical disorders ranging from undervirilized genitalia to complete pseudohermaphroditism [12,13]. Higher fertility and sexual maturation require normal testicular development, which is governed by chorionic gonadotropin in the uterus and after that by luteinizing hormone (LH) and follicle stimulating hormone (FSH) [14].…”
Section: Introductionmentioning
confidence: 99%
“…27 Estradiol also increases pituitary gland sensitivity to GnRH, which, in addition to its action to increase GnRH pulse frequency via positive feedback on the hypothalamic kisspeptin neurons, increases LH secretion. The increase in estradiol also suppresses FSH within the ovary to allow luteinization of the dominant follicle in the T A B L E 1 Clinical features of isolated gonadotropin deficiency in males and females Isolated LH deficiency 17 Isolated FSH deficiency 18 General presence of LH with subsequent ovulation. Progesterone, the dominant female hormone during the luteal phase, in contrast, slows LH pulse frequency, 28 inhibits proliferation and stimulates differentiation of endometrial cells.…”
Section: Sex Steroid Feedback On the Hypothalamus And Pituitarymentioning
confidence: 99%
“…Weiss et al [2] described for the first time in 1992 that the mutation of the luteinizing hormone β-subunit (LHB) gene can cause selective LH deficiency. At present, 10 male patients with LHB mutations have been reported globally, most of them showed delayed pubertal development and abnormal spermatogenesis [2][3][4][5][6][7][8][9]. In this study, the next-generation sequencing (NGS) combined with Sanger sequencing technology was used for the first time to screen and verify a new mutation site in the LHB gene.…”
mentioning
confidence: 99%
“…At present, eight different LHB gene mutations have been described in male selective LH deficiency, half of which occurred in consanguineous families. These genotypic abnormalities included the following: IVS2 + 1G→C mutation, which induced a gross abnormality in the processing of LHB mRNA [3]; deletion of nine bases in exon 2, which weakened the cystine knot folding motif [4]; c118_120del, which resulted in the loss of lysine at position 40 of the mature peptide [5]; and c.84G>A nonsense mutation, producing a truncated LHB peptide [6]. The genotypes of other sporadic cases were as follows: a missense mutation, which eliminated the receptor-binding activity [2]; a homozygous missense mutation in exon 2, which prevented the binding of heterodimer hormone to the receptor [7]; a compound heterozygous mutation, which impaired the maturation Chen J, et al Male hypogonadism of LHB peptide and disrupted splicing of the mRNA [8]; and a point deletion of the thymine nucleotide at position 215 in exon 3, which would cause a frameshift and premature termination at codon 128 [9] .…”
mentioning
confidence: 99%